Cigarette Smoke-Induced Lymphoid Neogenesis in COPD Involves IL-17/RANKL Pathway - Xiong, Jing; Zhou, Lu; Tian, Jieyu; Yang, Xia; Li, Yunsong; Jin, Rong; Le, Yanqing; Rao, Yafei; Sun, Yongchang (Frontiers in Immunology, 2021)
IL-17 is critical in lung lymphoid neogenesis in COPD, but the cellular and molecular mechanisms remain to be elucidated. Receptor activator of nuclear factor-κB ligand (RANKL) functions in lymphoid follicle formation in other organs, whether it is involved in IL-17A-dependent lymphoid neogenesis in COPD is unknown. To elucidate the expression and functional role of IL-17A/RANKL pathway in COPD. We first quantified and localized RANKL, its receptor RANK and IL-17A in lungs of patients with COPD, smokers and non-smokers. Next, IL17-/-and wild-type (WT) mice were exposed to air or cigarette smoke(CS) for 24 weeks, and lung lymphoid follicles and RANKL-RANK expression were measured. Lastly, we studied the in vitro biological function of RANKL pertaining to lymphoid neogenesis. We found that the expressions of RANKL-RANK and IL-17A, together with lymphoid follicles, were increased in lung tissues from patients with COPD. In WT mice exposed to CS, RANKL-RANK expressions were prominent in lung lymphoid follicles, which were absent in IL17 -/-mice exposed to CS. In the lymphoid follicles, RANKL + cellswere identified mostly as B cells and RANK was localized in dendritic cells(DCs). In vitro IL-17A increased the expressions of RANKL in B cells and RANK in DCs, which in turn responded to RANKL stimulation by upregulation of CXCL13. Altogether, these results suggest that B lymphocyte RANKL pathway is involved in IL-17A-dependent lymphoid neogenesis in COPD.